THE COLLAPSE OF ORDER. A MATTER OF EXASPERATION OR INSTRUMENTALIZATION? A HISTORIC RETROSPECTIVE ABOUT CONFESSIONAL DRIFT IN THE SYRIAN CONFLICT (Journal of the Spanish Institute for Strategic Studies, 2018)
The Civil war in Syria with its different protagonists, scenarios and all elements that make it up can´t be appropriately understood without a retrospective view on recent History. This article deals with a historic perspective about the perceptible confessional matter in Syria which is differentiated in three main periods: the end of the Ottoman Control, the Mandate and the Contemporary State- and has the goal or determining if religion plays an essential role within the conflict or if on the contrary religious beliefs have been used for all different sides as a political or social upheaval instrument. Moreover I will display elements that are considered characteristic in the context of the country´s current situation which have been present in Syria process for more than one and a half century